Systematic review of the stability and compatibility of propofol injection - Husna, Muftihatul; Munawiroh, Siti Z.; Puji Ekawati, Ratna; Hanifah, Suci (Anestezjologia Intensywna Terapia, 2021)
One ampoule of propofol is often divided into several syringes or is sometimes combined with other drugs that may lead to incompatibility and instability. A systematic review of literature (PubMed, Science Direct, and Google Scholar) identified 37 pieces of research which suggest that the data on propofol stability are limited. Results of all of the identified studies indicated that the stability of propofol is less than 24 hours. Additionally, the evidence shows that glass packaging as well as storing in cold and dark conditions promote stability. What is more, propofol was proved to be incompatible with 23 of the 36 drugs tested. In conclusion, there is a relatively small body of literature that measures the physical stability of propofol. The findings of this review recommend keeping propofol in glass and storing it no longer than 24 hours. Compatibility data must be considered in co-administrations with propofol.